A new species of Agave subgenus Littaea (Agavaceae) of the state of Querétaro, Mexico - Galván, Raquel; Zamudio, Sergio (Instituto de Ecología, A.C., 2013)
Agave gracielae sp. nov. from the states of Querétaro and San Luis Potosí is described. This species has characteristics that include it in the Striatae Baker group. Within this group it is related to A. dasylirioides Jacobi & Bouché, A. petrophila García-Mendoza & E. Martínez and A. rzedowskiana P. Carrillo, Vega & R. Delgad. The species is found on limestone rocky outcrops in oak-pine wood or montane rain forest.